The Effects of Anxiety and Emotional Intelligence on The Mathematic Learning Outcomes of Fifth Grade Students - Ni Komang Reza Cahyani; I Gusti Agung Ayu Wulandari (Indonesian Journal Of Educational Research and Review, 2021)
Students experience very high anxiety, so it impacts the difficulty of digesting and understanding mathematics learning materials. It causes low Mathematics learning outcomes. This study analyzes the effect of anxiety and emotional intelligence on fifth-grade elementary school students' mathematics learning outcomes. This study was an "ex post facto" study with a population of 238 students. The sample was determined using a proportional random sampling technique to obtain a total sample of 142 students. The techniques used to collect data were observation, interviews, questionnaires, document recording, and tests. The instrument used to collect data was a questionnaire. Hypothesis testing was carried out using simple regression analysis techniques and multiple regression analysis. The results of this study indicate that: There is an influence of anxiety on mathematics learning outcomes with a contribution of 3.5%; There is an influence of emotional intelligence on mathematics learning outcomes with a contribution of 6.6%; There is an influence of anxiety and emotional intelligence on mathematics learning outcomes with a contribution of 7.2%. So the conclusion of the research shows a significant influence between anxiety and emotional intelligence on the mathematics learning outcomes of fifth-grade elementary school students.